GhSOC1s Evolve to Respond Differently to the Environmental Cues and Promote Flowering in Partially Independent Ways - Ma, Limei; Yan, Yuanyuan (Frontiers in Plant Science, 2022)
Gossypium hirsutum is most broadly cultivated in the world due to its broader adaptation to the environment and successful breeding of early maturity varieties. However, how cotton responds to environmental cues to adjust flowering time to achieve reproductive success is largely unknown. SOC1 functions as an essential integrator for the endogenous and exogenous signals to maximize reproduction. Thus we identified six SOC1-like genes in Gossypium that clustered into two groups. GhSOC1-1 contained a large intron and clustered with monocot SOC1s, while GhSOC1-2/3 were close to dicot SOC1s. GhSOC1s expression gradually increased during seedling development suggesting their conserved function in promoting flowering, which was supported by the early flowering phenotype of 35S:GhSOC1-1 Arabidopsis lines and the delayed flowering of cotton silencing lines. Furthermore, GhSOC1-1 responded to short-day and high temperature conditions, while GhSOC1-2 responded to long-day conditions. GhSOC1-3 might function to promote flowering in response to low temperature and cold. Taken together, our results demonstrate that GhSOC1s respond differently to light and temperature and act cooperatively to activate GhLFY expression to promote floral transition and enlighten us in cotton adaptation to environment that is helpful in improvement of cotton maturity.